Pull in and Push Out: Mechanisms of Horizontal Gene Transfer in Bacteria - Sun, Dongchang (Frontiers in Microbiology, 2018)
Horizontal gene transfer (HGT) plays an important role in bacterial evolution. It is well accepted that DNA is pulled/pushed into recipient cells by conserved membrane-associated DNA transport systems, which allow the entry of only single-stranded DNA (ssDNA). However, recent studies have uncovered a new type of natural bacterial transformation in which double-stranded DNA (dsDNA) is taken up into the cytoplasm, thus complementing the existing methods of DNA transfer among bacteria. Regulated by the stationary-phase regulators RpoS and cAMP receptor protein (CRP), E. coli establishes competence for natural transformation with dsDNA, which occurs in agar plates. To pass across the outer membrane, a putative channel, which may compete for the substrate with the porin OmpA, may mediate the transfer of exogenous dsDNA into the cell. To pass across the inner membrane, dsDNA may be bound to the periplasmic protein YdcS, which delivers it into the inner membrane channel formed by YdcV. The discovery of cell-to-cell contact-dependent transformation implies the presence of additional mechanism(s) of transformation. This review will summarize the current knowledge about mechanisms of HGT with an emphasis on recent progresses regarding non-canonical mechanisms of natural transformation. Fully understanding the mechanisms of HGT will provide a foundation for monitoring and controlling multidrug resistance.